Is thyroid hormone supplementation avoidable for patients with low‐risk papillary thyroid cancer after thyroid lobectomy? A two‐center observational study. (16th August 2021) - Xiao, Liu; Wu, Jie; Jiang, Lisha; Xu, Yangmengyuan; Liu, Bin
Abstract: Objective: Changing insights regarding the extent of surgery for low‐risk papillary thyroid cancer (PTC) stir up discussions on the benefits and harms of thyroid lobectomy versus total thyroidectomy. The chance of needing postoperative thyroid hormone supplementation after thyroid lobectomy is still unclear. The purpose of this retrospective two‐center study was to identify the incidence and risk factors of postoperative thyroid‐stimulating hormone (TSH) elevation (>2.0 μIU/ml) after thyroid lobectomy for low‐risk PTC. Design and Methods: Medical records of 201 consecutive patients with low‐risk PTC from two tertiary centers who underwent thyroid lobectomy between 2015 and 2019 were retrospectively reviewed. Postoperative thyroid function tests were measured regularly and patients were prescribed levothyroxine if the TSH level was higher than 2.0 μIU/ml. Multivariable regression models were used to evaluate potential risk factors associated with postoperative TSH elevation after thyroid lobectomy. Results: At 6 weeks postoperatively, 85% had TSH level of >2 μIU/ml; this increased to 88% by 3–6 months. Receiver operating characteristic analysis identified preoperative TSH cut‐off (>1.7 μIU/ml) to predict postoperative TSH elevation. Multivariate analysis revealed that only a high preoperative TSH level (>1.7 μIU/ml) was an independent risk factor for a postoperative TSH level of >2 μIU/ml (odds ratio = 7.71; p  < .001). Conclusion: Nearly 90% of the patients who underwent thyroid lobectomy for low‐risk PTC had a postoperative TSH level of >2 μIU/ml, necessitating thyroid hormone supplementation in accordance with current guidelines. This finding highlights that preoperative patient counseling should also focus on raising awareness about postoperative thyroid hormone supplementation for low‐risk PTC patients seeking thyroid lobectomy.